Protective Effect of Pantethine on Experimental Thrombocytopenia in the Rat - Ashida, Shin-ichiro; Abiko, Yasushi (Thrombosis and Haemostasis, 1975)
The effects of pantethine on circulating platelet counts and platelet functions were studied in normal and experimentally produced thrombocytopenic rats.Administration of pantethine to normal animals did not cause any alterations in both platelet count and function except for a slight enhancement of intravascular platelet aggregation induced by collagen or neuraminidase.Injection of anti-rat platelet rabbit serum into rats resulted in acute thrombocytopenia. Administration of pantethine prior to the antiserum promoted recovery from the thrombocytopenia in a dose dependent manner, but administration of the drug after development of the thrombocytopenia was not effective. A similar result was obtained with a transient thrombocytopenia induced by exchange transfusion with platelet poor blood. Regardless of whether animals were treated with pantethine or not, the platelets newly generated during the course of recovery from thrombocytopenia were essentially normal in the function tested in vitro.A more chronic thrombocytopenia induced by repeated injections of the antiserum was prevented, to some significant degree, by daily administration of pantethine throughout the experimental period.In contrast to these, such effect of pantethine was not observed with the thrombocytopenia models produced by nitrogen mustard N-oxide and neuraminidase.These findings were discussed in relation to mechanism of the action of pantethine and to possible clinical application of the drug to thrombocytopenia.